A rational quantitative optimal approach to dam safety risk reduction. Issue 2 (2nd April 2016) - Cloete, G.C.; Retief, J.V.; Viljoen, C.
ABSTRACT: The rational quantitative optimal (RQO) approach presents a robust risk evaluation model which produces a definitive result for the reduction of risk from overtopping of earth-fill dams. The model is based on principles of risk, but an analysis of a portfolio of dams provides discrete optimal results, not expressed in terms of probability. All the steps that the methodology comprises have been developed exhaustively and propose to address concerns raised by dam owners and decision-makers regarding risk-based dam safety: a transparent framework for decision-making related to public safety, which will also appeal to the technically minded portfolio manager looking for a purely quantitative procedure to assist in the decision-making process. The RQO process is applied mechanistically, not requiring judgement from the decision-maker. In so doing it addresses the concern raised by dam owners regarding the judgmental probability of risk assessment. Risk in this paper is associated with embankment dams and external erosion, which is the single largest cause of failure of these dams. Also, in the context of this article, 'optimal' refers to maximising lives saved over a portfolio of dams under the constraint of limited resources.